2022
DOI: 10.3390/nano12172919
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Recent Progress in Nanofiber Membranes for Oily Wastewater Treatment

Abstract: Oil separation from water becomes a challenging issue in industries, especially when large volumes of stable oil/water emulsion are discharged. The present short review offers an overview of the recent developments in the nanofiber membranes used in oily wastewater treatment. This review notes that nanofiber membranes can efficiently separate the free-floating oil, dispersed oil and emulsified oil droplets. The highly interconnected pore structure nanofiber membrane and its modified wettability can enhance the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 139 publications
0
6
0
Order By: Relevance
“…Consequently, they exhibit distinctive electrical and physical properties, including high surface‐to‐volume ratio, lightweight, unique porous structure, interconnected porosity, and the potential for incorporating chemical functionalities. As a result of these characteristics, nanofibers have garnered significant attention in recent decades [82–85] . Also used for osmotic energy [86–92] .…”
Section: Various Materials For Osmotic Energy Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they exhibit distinctive electrical and physical properties, including high surface‐to‐volume ratio, lightweight, unique porous structure, interconnected porosity, and the potential for incorporating chemical functionalities. As a result of these characteristics, nanofibers have garnered significant attention in recent decades [82–85] . Also used for osmotic energy [86–92] .…”
Section: Various Materials For Osmotic Energy Conversionmentioning
confidence: 99%
“…As a result of these characteristics, nanofibers have garnered significant attention in recent decades. [82][83][84][85] Also used for osmotic energy. [86][87][88][89][90][91][92] Wang et al [93] reported the synthesis of highly flexible and mechanically robust carbonaceous ordered mesoporous nanowires (CMWs) based on arrays of nanofibers using a simple and straightforward soft-templating hydrothermal carbonization approach.…”
Section: Polymersmentioning
confidence: 99%
“…Membrane-based liquid separation processes have substantial roles in industries such as food processing, pharmaceuticals, and petrochemicals [ 1 , 2 , 3 , 4 , 5 , 6 ]. Over the last two decades, membrane technology has also been increasingly employed to address water scarcity issues through wastewater reclamation and desalination [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the purification efficiency of oily wastewater, three main techniques have been developed: flotation, (electro/chemical) coagulation, and utilization of organic solvent filtration membranes [2c,3] . Among these methods, the membrane‐based separation technology is of particular interest given its many advantages, including its simplicity, low operation cost, great separation efficiency, continuous operation capability, and low energy consumption [1a,4] . The membranes could be easily fabricated to exhibit the oleophilic property for effective oil/water separation applications.…”
Section: Introductionmentioning
confidence: 99%
“…This method involves the utilization of the voltage difference between the tip and the collector after preparing a polymer precursor solution. It can precisely tune the diameter of nanofibers and can be easily controlled by several electrospinning parameters, including the miscibility of the solvent and polymer, applied voltage, viscosity, the solution conductivity [1a,9d,10] . In addition, the degree of porosity and pore size of the nanofibers can also be tuned by the electrospinning conditions.…”
Section: Introductionmentioning
confidence: 99%